Machine learning and artificial intelligece - Joshi, Ameet V (Switzerland: Springer Nature, 2020)
The book provides comprehensive coverage of combined AI and ML theory and applications. Rather than looking at the field from only a theoretical or only a practical perspective, this book unifies both perspectives to give holistic understanding. The first part introduces the concepts of AI and ML and their origin and current state. The second and third parts delve into conceptual and theoretic aspects of static and dynamic ML techniques. The fourth part describes the practical applications where presented techniques can be applied. The fifth part introduces the user to some of the implementation strategies for solving real life ML problems. Each chapter is accompanied with a set of exercises that will help the reader / student to apply the learnings from the chapter to a real-life problem.
Part I Introduction -- Part II. Machine Learning -- Part III. Building end to end pipelines -- Part IV. Artificial intelligence -- Part V. Implementations -- Part VI. Conclusion
Includes bibliography and index
Keywords: Computer Science; Machine Learning; Artificial Intelligence